Preparation method of alginate-based hydrogel colorimetric label
Through step-by-step cross-linking synergistic solvent induction process and ultrasonic treatment, the porous dual network structure of alginate hydrogel was constructed, which solved the problems of low elastic modulus and uneven color rendering, significantly improved the manufacturability and measurement accuracy of colorimetric labels, and promoted its market-oriented application.
Patent Information
- Application Number
- CN202411877617.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The elastic modulus of alginate hydrogel-based colorimetric labels is low and the color rendering is uneven, which affects its manufacturability and measurement accuracy and limits its market-oriented application.
Through step-by-step cross-linking and solvent induction process, an interconnected through porous dual network structure of alginate hydrogel is constructed, and the distribution of free water inside the hydrogel is regulated through ultrasonic treatment.
It significantly improves the elastic modulus and colorimetric resolution of colorimetric labels, improves its manufacturability and measurement accuracy, and promotes the market-oriented application of alginate hydrogel-based colorimetric indicator labels.
Smart Images

Figure CN119661885A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of food packaging, and in particular relates to a method for preparing an alginate-based hydrogel colorimetric label. Background Art
[0002] With the development of science and technology, people's demand for food safety and quality continues to increase. Due to various physical, chemical and biological factors, fresh food loses its nutritional value or even deteriorates during transportation, storage and distribution, posing a major risk to human health and the environment. Smart packaging that can trace the source and monitor the freshness of food in real time can effectively provide information on real-time changes in food quality and improve product safety and quality by providing early warning of potential problems.
[0003] Colorimetric indicator labels are a type of simple, efficient, and low-cost gas sensor that can change the color of the label in response to external stimuli to indicate changes in food quality. Colorimetric labels are usually composed of two parts: a solid support layer and an indicator combined with it. Alginate hydrogel is a natural biomaterial with the advantages of low cost, biosafety, and environmental friendliness, and is a relatively good solid support layer material.
[0004] Alginate hydrogels have poor mechanical properties and are easily soluble in water, which brings certain limitations to their actual production and application. Currently, many studies focus on alginate aerogel colorimetric labels. However, aerogels lose their advantage of being easy to react with gases due to the removal of water. Alginate hydrogels containing a certain amount of free water and bound water are themselves a pH-sensitive material, and have rich ion channels and pore structures that provide more reaction sites for detecting gases and indicators attached to them, thus having higher sensitivity to gases volatile from various foods.
[0005] At present, there are two key problems in the research of hydrogel-based colorimetric labels: one is that the elastic modulus of hydrogel is low, and the other is that the colorimetric labels have the problem of uneven color development, that is, low resolution. These two problems affect the manufacturability and accuracy of hydrogel-based colorimetric labels, thus limiting their market application in packaging. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present disclosure is to provide a method for preparing an alginate-based hydrogel colorimetric label. The present disclosure can improve the manufacturability and measurement accuracy of alginate-based colorimetric indicator labels, thereby promoting the market application of alginate hydrogel-based colorimetric indicator labels.
[0007] To achieve the above objectives, the present disclosure provides the following technical solutions: A method for preparing an alginate-based hydrogel colorimetric label, the method comprising: adding alginate and a regulating material in a set ratio to an aqueous solution containing an indicator solution and glycerol, stirring and heating the solution to obtain a mixed solution; preparing the mixed solution into an alginate hydrogel film based on a film casting method or a tape casting method; uniformly spraying or coating a metal ion crosslinking agent on the surface of the alginate hydrogel film to perform a crosslinking treatment, and obtaining a crosslinked alginate hydrogel film after standing; immersing the crosslinked alginate hydrogel film in an ethanol solution, and obtaining an alginate-based hydrogel colorimetric label after solvent exchange induction with the aid of ultrasound.
[0008] Optionally, the alginate includes sodium alginate or oxidized sodium alginate.
[0009] Optionally, the regulating material comprises gelatin or agar.
[0010] Optionally, the indicator solution is prepared by dissolving the indicator in anhydrous ethanol or an aqueous solution.
[0011] Optionally, the indicator includes any one or two of the following: methyl red, bromothymol blue, methylene blue, bromocresol purple and anthocyanin.
[0012] Optionally, the metal ion cross-linking agent includes any one of the following: a calcium ion solution, an aluminum ion solution and a zinc ion solution.
[0013] Optionally, the concentration of the metal ion cross-linking agent is 0.25 mol / L to 0.5 mol / L.
[0014] Optionally, the metal ion cross-linking agent is sprayed or coated on the surface of the sodium alginate hydrogel film for a standing time of 10 min to 60 min after the cross-linking treatment.
[0015] Optionally, the concentration of the ethanol solution is 10% v / v to 30% v / v.
[0016] Optionally, the auxiliary ultrasound time is 0.5 h to 3 h.
[0017] Compared with the prior art, the beneficial effects brought about by the present disclosure are as follows: the present disclosure can construct an interconnected porous double network structure of alginate hydrogel through a step-by-step cross-linking and solvent-induced process, and can also regulate the distribution of free water inside the hydrogel, and can improve the elastic modulus and colorimetric resolution of the colorimetric label. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic flow chart of a method for preparing an alginate-based hydrogel colorimetric label provided by one embodiment of the present disclosure; Figure 2This is the microstructure result diagram of the surface and cross section of sodium alginate and its composite hydrogel film before induction; Figure 3 The microstructure results of the surface and cross section of the induced sodium alginate and its composite hydrogel film are shown in FIG. Figure 4 This is the laser confocal observation result of sodium alginate and its composite hydrogel film before induction; Figure 5 This is the laser confocal observation result of the induced sodium alginate and its composite hydrogel film; Figure 6 is the elastic modulus result diagram of sodium alginate and its composite hydrogel before induction; Figure 7 This is the elastic modulus result diagram of sodium alginate and its composite hydrogel after induction; Figure 8 This is a comparison chart of the elastic modulus of a sodium alginate-based hydrogel sample prepared by the method described in the present application and a sodium alginate-based hydrogel sample from other sources; Fig. 9 This is the colorimetric response result diagram of sodium alginate and its composite hydrogel before induction; Fig.10 This is the colorimetric response result diagram of sodium alginate and its composite hydrogel after induction; Fig.11 This is the sensitivity result diagram of sodium alginate and its composite hydrogel before induction; Fig.12 This is the sensitivity result diagram of sodium alginate and its composite hydrogel after induction; Fig.13 It is a comparison chart of the quantitative results of color uniformity of sodium alginate and its composite hydrogel before and after the induction process. DETAILED DESCRIPTION
[0019] The following will refer to the attached Figures 1 to 13 Specific embodiments of the present disclosure are described in detail. Although specific embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0020] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present disclosure, but the description is based on the general principles of the specification and is not used to limit the scope of the present disclosure. The scope of protection of the present disclosure shall be determined by the attached claims.
[0021] To facilitate understanding of the embodiments of the present disclosure, further explanation will be given below using specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present disclosure.
[0022] Figure 1 FIG. 1 is a schematic diagram of a method for preparing an alginate-based hydrogel colorimetric label provided by an exemplary embodiment of the present disclosure. Figure 1 As shown, the preparation method comprises the following steps: S1: A 1% v / v methyl red indicator aqueous solution and a 1.5% v / v glycerol aqueous solution were mixed to obtain a mixed solvent, and then sodium alginate and gelatin in a mass ratio of 1:1 were added to the mixed solvent, heated to 60° C., and magnetically stirred for 2 h to obtain a 4 wt % mixed solution; In this step, the methyl red indicator is prepared by dissolving 100 mg of methyl red powder in 100 mL of anhydrous ethanol.
[0023] S2: preparing the mixed solution into a sodium alginate hydrogel film (SA / Gel, Sodium Alginate / Gelatin) by a casting method or a tape casting method; In this step, a sodium alginate hydrogel film is prepared by a casting method, which specifically includes: Prepare the mold: Select a mold of appropriate size and flatness, usually a flat plate, and ensure its surface is clean and smooth.
[0024] Pouring solution: Pour the stirred alginate-based mixed solution slowly and evenly into the mold, taking care to avoid introducing bubbles.
[0025] Standing and evaporation: Let the solution stand naturally at room temperature or controlled temperature for a period of time, during which the solvent will gradually evaporate to form a wet film with a certain thickness.
[0026] Drying and curing: If necessary, the film can be further dried in the air or placed in an oven for low-temperature drying to completely cure the film.
[0027] The coating or Doctor Blade Method is used to prepare the sodium alginate hydrogel film, which specifically includes: Set up equipment: Adjust the blade gap on the casting machine to the desired film thickness and prepare the conveyor belt or support plate.
[0028] Coating solution: Use a doctor blade or similar tool to evenly coat the mixed solution on a moving support surface. The final thickness of the film can be controlled by adjusting the blade height.
[0029] Drying process: As the support plate moves, the solvent in the solution evaporates rapidly, leaving a uniform wet film; the drying process can then be accelerated by heating or other means to quickly set the film.
[0030] Collect the film: When the film is fully dried and has sufficient mechanical strength, it is peeled off from the support plate to complete the preparation.
[0031] S3: uniformly spraying or coating a calcium ion solution (such as a calcium chloride solution) with a concentration of 0.25 mol / L on the surface of the sodium alginate hydrogel film, and performing a cross-linking treatment at room temperature. After standing for 10 minutes, a sodium alginate hydrogel film after the cross-linking treatment is obtained; In this step, alginate molecules contain a large number of carboxyl groups (~COOH). + When the calcium ion is uniformly sprayed or coated on the surface of the sodium alginate hydrogel film, the calcium ion will form a complex bond with the carboxyl group. Each calcium ion can form a cross-linking point with multiple carboxyl groups, thereby connecting multiple alginate molecules together to form a three-dimensional network structure. This three-dimensional network structure significantly enhances the mechanical properties of the hydrogel, improves its elastic modulus and mechanical strength, and reduces the swelling and fluidity of the hydrogel.
[0032] S4: Place the cross-linked sodium alginate hydrogel film into a 10% v / v ethanol solution at room temperature, and ensure that the sodium alginate hydrogel film is completely immersed in the ethanol solution. Place the container containing the sodium alginate hydrogel film and the ethanol solution in an ultrasonic cleaner for ultrasonic treatment. The ultrasonic power is set to 600 W and the ultrasonic time is set to 0.5 h. After the ultrasonic treatment is completed, take out the sodium alginate hydrogel film from the ethanol solution and obtain the sodium alginate-based hydrogel colorimetric label after drying.
[0033] In this step, when the ultrasonic wave propagates in the solution, a cavitation effect will be generated, that is, the tiny bubbles in the solution are rapidly formed, grown and collapsed, and the collapse of these bubbles will produce strong local pressure and flow, which helps to accelerate the diffusion and exchange of solvent molecules. Through ultrasonic treatment, ethanol molecules can penetrate into the interior of the sodium alginate hydrogel film faster, and at the same time, the free water molecules in the sodium alginate hydrogel film are replaced, which not only shortens the time of solvent exchange, but also improves the efficiency of exchange. In addition, the strong local flow generated by the ultrasonic wave helps to evenly disperse the solvent molecules and reduce the uneven distribution of the solvent inside the sodium alginate hydrogel film. The sodium alginate hydrogel film after ultrasonic treatment is more uniform in color response, which can significantly improve the resolution and accuracy of the colorimetric label. Further, the mechanical vibration of the ultrasonic wave helps to tightly arrange the polymer chains inside the sodium alginate hydrogel film, improve the structural stability of the film, and make the sodium alginate hydrogel film after ultrasonic treatment have better mechanical strength and durability, and is not easy to break or deform.
[0034] It should be noted that if the sodium alginate hydrogel film is not ultrasonically treated, the solvent exchange process mainly relies on natural diffusion, so that the free water inside the sodium alginate hydrogel film cannot be completely replaced by ethanol, which in turn causes the physical properties of the sodium alginate hydrogel film (such as elastic modulus and mechanical strength) to fail to meet the requirements. In addition, the uneven distribution of the solvent inside the sodium alginate hydrogel film will lead to uneven distribution of the color developer in the film, which will cause the color change of the colorimetric label when responding to the target gas to be uneven, thereby affecting the resolution and accuracy of the colorimetric label.
[0035] In another exemplary embodiment, the present disclosure also provides a method for preparing an alginate-based hydrogel colorimetric label, the method comprising the following steps: S10: 1% v / v bromothymol blue indicator aqueous solution and 2% v / v glycerol aqueous solution are mixed to obtain a mixed solvent, and then oxidized sodium alginate and gelatin in a mass ratio of 1:5 are added to the mixed solvent, heated to 70° C., and magnetically stirred for 2 h to obtain an 8 wt % mixed solution; In this step, the bromothymol blue indicator is prepared by dissolving 100 mg of bromothymol blue powder in 100 mL of anhydrous ethanol.
[0036] S20: preparing a sodium alginate hydrogel film from the mixed solution by a film casting method or a casting method; S30: uniformly spraying or coating an aluminum ion solution (such as aluminum chloride solution) with a concentration of 0.3 mol / L on the surface of the sodium alginate hydrogel film, and performing a cross-linking treatment at room temperature. After standing for 30 minutes, a cross-linked sodium alginate hydrogel film is obtained; S40: placing the cross-linked sodium alginate hydrogel film into an ethanol solution with a concentration of 20% v / v at room temperature, and ensuring that the sodium alginate hydrogel film is completely immersed in the ethanol solution, placing the container containing the sodium alginate hydrogel film and the ethanol solution in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic power is set to 600 W, and the ultrasonic time is set to 2 h. After the ultrasonic treatment is completed, the sodium alginate hydrogel film is taken out from the ethanol solution, and the sodium alginate hydrogel colorimetric label is obtained after drying.
[0037] In another exemplary embodiment, the present disclosure also provides a method for preparing an alginate-based hydrogel colorimetric label, the method comprising the following steps: S100: A 10% v / v anthocyanin indicator aqueous solution and a 10% v / v glycerol aqueous solution were mixed to obtain a mixed solvent, and then sodium alginate (SA) and agar in a mass ratio of 1:9 were added to the mixed solvent, heated to 80° C., and magnetically stirred for 2 h to obtain a 9 wt % mixed solution; In this step, the anthocyanin indicator is prepared by dissolving 100 mg of anthocyanin powder in 100 mL of deionized water.
[0038] In addition, methylene blue and bromocresol purple can also be used as indicators.
[0039] S200: preparing a sodium alginate hydrogel film from the mixed solution by a film casting method or a tape casting method; S300: uniformly spraying or coating a zinc ion solution (such as a zinc chloride solution) with a concentration of 0.5 mol / L on the surface of the sodium alginate hydrogel film, and performing a cross-linking treatment at room temperature. After standing for 60 minutes, a sodium alginate hydrogel film after the cross-linking treatment is obtained; S400: placing the cross-linked sodium alginate hydrogel film into a 30% v / v ethanol solution at room temperature, and ensuring that the sodium alginate hydrogel film is completely immersed in the ethanol solution, placing the container containing the sodium alginate hydrogel film and the ethanol solution in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic power is set to 600 W, and the ultrasonic time is set to 3 hours. After the ultrasonic treatment is completed, the sodium alginate hydrogel film is taken out from the ethanol solution, and after drying, a sodium alginate-based hydrogel colorimetric label is obtained.
[0040] In the above embodiment, the concentration of the metal ion crosslinking agent (i.e., calcium ion solution, aluminum ion solution, and zinc ion solution) is 0.25 mol / L to 0.5 mol / L, wherein 0.25 mol / L is the lowest effective concentration, which enables the metal ions to fully crosslink with the carboxyl groups in the alginate. At this concentration, the number of metal ions is sufficient to form sufficient crosslinking points to enhance the structural stability and mechanical properties of the hydrogel. 0.5 mol / L is the highest effective concentration, which can provide a stronger crosslinking effect, further improve the mechanical properties of the hydrogel, and avoid the negative effects of excessive concentration. If the concentration is too low (less than 0.25 mol / L), the crosslinking effect will be insufficient, resulting in insufficient mechanical properties of the hydrogel, which is prone to rupture or deformation during use. If the concentration is too high (greater than 0.5 mol / L), although the crosslinking effect will be better, the excessive concentration may lead to the following adverse effects: First, excessive metal ions will cause the hydrogel to be over-crosslinked, making it too rigid and losing the necessary flexibility and elasticity; second, high concentrations of metal ions will damage the structure of the hydrogel, causing the film to become fragile and easy to rupture. Furthermore, the present application uses 0.3 mol / L as the optimal concentration of the metal crosslinker because: a concentration of 0.3 mol / L can provide sufficient metal ions for an effective crosslinking reaction to enhance the structural stability and mechanical properties of the hydrogel while maintaining appropriate flexibility and elasticity. This concentration will neither cause insufficient crosslinking due to too low a concentration nor make the hydrogel too rigid due to too high a concentration. After testing, this concentration can achieve the optimal response speed and accuracy of the indicator to the target gas (such as ammonia) while ensuring the stability of the hydrogel network structure.
[0041] In the above embodiment, the standing time after the metal ion crosslinking agent is sprayed or coated on the surface of the sodium alginate hydrogel film for crosslinking treatment is set to 10 to 60 minutes, wherein 10 minutes is the shortest effective time, during which the metal ions can penetrate into the surface of the film and form preliminary crosslinking points with the carboxyl groups. 60 minutes is the longest effective time, during which the metal ions have enough time to penetrate into the interior of the film, form crosslinking points with more carboxyl groups, and enhance the structural stability and mechanical properties of the film. If the time is too short (<10 minutes), firstly, the crosslinking reaction will be insufficient, so that the mechanical properties of the hydrogel are insufficient, and it is easy to break or deform during use; secondly, due to the presence of free water, the response time of the hydrogel to the target gas will be prolonged and the sensitivity will be reduced. If the time is too long (>60 minutes), the hydrogel will be over-crosslinked, making it too rigid and losing the necessary flexibility and elasticity. In addition, the long-term crosslinking reaction will also damage the structure of the hydrogel, causing the sodium alginate hydrogel film to become fragile and easy to break. Further, the present application uses 30 minutes as the optimal standing time because, within 30 minutes, the metal ions have enough time to penetrate into the interior of the sodium alginate hydrogel film and form crosslinking points with more carboxyl groups, which helps to enhance the structural stability and mechanical properties of the film and ensure that the crosslinking effect reaches the ideal state. If the standing time is shorter than 30 minutes, the metal ions may not have enough time to penetrate into the interior of the sodium alginate hydrogel film and form sufficient crosslinking points with the carboxyl groups, which will cause the crosslinking network to be not dense enough, thereby relatively weakening the structural stability and mechanical properties of the hydrogel. If the standing time is greater than 30 minutes, the possibility of excessive crosslinking of the hydrogel will be relatively increased, making it too rigid and losing the necessary flexibility and elasticity. This excessive crosslinking will not only affect the feel and use experience of the material, but may also cause damage to the hydrogel structure, making the film fragile and brittle.
[0042] In the above embodiment, the concentration of the ethanol solution is set to 10% v / v to 30% v / v, wherein, experimentally verified, 10% v / v is the lowest effective concentration, at which the number of ethanol molecules is sufficient to start the solvent exchange process, but will not affect the physical properties of the film too much. 30% v / v is the highest concentration, at which the number of ethanol molecules is sufficient to completely replace the free water and improve the physical properties of the film. In addition, if the concentration is too low (<10% v / v), the solvent exchange effect will be insufficient, and the free water inside the sodium alginate hydrogel film cannot be completely replaced, which will cause the indicator inside the film to be unevenly distributed, resulting in inconsistent color changes, affecting the resolution and accuracy of the colorimetric label. On the contrary, if the concentration is too high (>30% v / v), the sodium alginate hydrogel film will be overly dehydrated, making it dry, hard and brittle, and losing the necessary flexibility. In addition, excessive ethanol will affect the activity of the indicator and reduce its responsiveness to the target gas.
[0043] In summary, the concentration of the ethanol solution is set at 10% v / v to 30% v / v to ensure that the solvent exchange process is sufficient but not excessive, while avoiding adverse effects on the physical properties and structure of the film. The ethanol concentration within this range can balance the solvent exchange effect and the physical properties of the film, ensuring that the prepared alginate-based colorimetric indicator label has good physical properties and color response.
[0044] In the above embodiment, the ultrasonic treatment time is set to 0.5h~3h after experimental verification, wherein 0.5h is the minimum effective treatment time, during which the ultrasonic wave can significantly accelerate the penetration of ethanol molecules into the interior of the sodium alginate hydrogel film and preliminarily displace free water. 3h is the maximum treatment time, during which the ethanol molecules can thoroughly penetrate into the film and displace free water to the maximum extent. It has been tested that if the ultrasonic time is too short (less than 0.5h), the solvent exchange will be insufficient, that is, there will still be a lot of free water inside the sodium alginate hydrogel film that has not been replaced, which will affect the physical properties of the sodium alginate hydrogel film, including elastic modulus and mechanical strength. In addition, due to the presence of free water, the response time of the sodium alginate hydrogel film to the target gas will also be prolonged, resulting in a decrease in the sensitivity of the indicator tag. On the contrary, if the ultrasonic time is too long (greater than 3h), firstly, the polymer chains inside the sodium alginate hydrogel film will break, making the sodium alginate hydrogel film fragile and prone to rupture; secondly, excessive ethanol penetration will cause excessive dehydration of the sodium alginate hydrogel film, making it dry, hard and brittle, and losing the necessary flexibility, which will affect the activity of the indicator and reduce its response to the target gas.
[0045] In summary, the ultrasonic treatment time is set to 0.5h to 3h, in order to ensure that the solvent exchange is fully carried out, while avoiding damage to the sodium alginate hydrogel film structure, so as to ensure that the prepared alginate-based colorimetric indicator label has good physical properties and color response. Further, the application uses 2h as the optimal ultrasonic treatment time, because, within the range of 0.5h to 3h, the time point of 2h can ensure that the ethanol molecules fully penetrate into the inside of the sodium alginate hydrogel film, and replace free water to the maximum extent, which helps to improve the physical properties of the film, such as elastic modulus and mechanical strength, while ensuring the uniform distribution of the indicator in the film. If the ultrasonic treatment exceeds 2h, the polymer chain inside the sodium alginate hydrogel film may be broken, making the film fragile and prone to rupture. In addition, long-term ultrasonic treatment may also cause excessive dehydration of the film, making it dry, hard and brittle, losing the necessary flexibility, affecting its practical application performance. In summary, 2 h is taken as the optimal ultrasonic treatment time because it can ensure sufficient solvent exchange while avoiding damage to the sodium alginate hydrogel film structure, thereby ensuring that the prepared alginate-based colorimetric indicator label has good physical properties and color response.
[0046] This application uses a confocal laser microscope (Leica TCS SP8 STED) and an Olympus large metallographic microscope (OLYMPUS~GX71) to compare and analyze the surface and cross-section of sodium alginate hydrogel films before and after induction. Sample SA is a sodium alginate hydrogel film, and samples SG1, SG2, and SG3 represent sodium alginate and gelatin ratios of 3:1, 1:1, and 1:3, respectively. Among them, Figure 2 This is the microstructure result diagram of the surface and cross section of sodium alginate and its composite hydrogel film before induction; Figure 3 The above results show that the distribution of the pore structure shapes on the surface and cross section of the sodium alginate and its composite hydrogel film before induction is significantly different, with the cross section surface showing larger pores. After induction, the pores on the surface tend to be dense and uniform, and larger pores appear on the cross section.
[0047] Figure 4 This is the laser confocal observation result of sodium alginate and its composite hydrogel film before induction; Figure 5 This is the laser confocal observation result of the induced sodium alginate and its composite hydrogel film. Figure 4 It shows that the distribution of the color developer on the surface of the sodium alginate composite hydrogel film before induction is uneven. Figure 5The cross-sectional distribution of the chromogen in the sodium alginate hydrogel film (SA) after induction is uneven, while the surface and cross-sectional distribution of the chromogen in the sodium alginate composite hydrogel film (SA / Gel) after induction is more uniform throughout the hydrogel. The above results show that after the induction process, the structure and chromogen distribution of the sodium alginate composite hydrogel film are more uniform.
[0048] This application also made a comparative analysis of the mechanical properties of sodium alginate and its composite hydrogel film before and after induction. The mechanical properties of the hydrogel were characterized by a universal tensile machine (UTM2103, Shenzhen Sansi) at room temperature (25°C) and a humidity of 75% RH. For the tensile test, the hydrogel was cut into 50 mm × 10 mm × 2 mm specimens at a stretching speed of 50 mm / min. The elastic modulus was calculated using the slope of the initial linear region of the stress-strain curve (strain 5-10%). Among them, Figure 6 is the elastic modulus result diagram of sodium alginate and its composite hydrogel before induction; Figure 7 This is the elastic modulus result diagram of sodium alginate and its composite hydrogel after induction; Figure 8 This is a comparison chart of the elastic modulus of the sodium alginate-based hydrogel samples prepared by the method described in the present application and the sodium alginate-based hydrogel samples from other sources. Figure 6 In the figure, the slope of the stress-strain curve of sodium alginate and its composite hydrogel before induction is small in the initial linear region (strain 5% to 10%), indicating that the stiffness of sodium alginate and its composite hydrogel before induction is low. Figure 7 In the experiment, the slope of the stress-strain curve of the induced sodium alginate and its composite hydrogel in the initial linear region (strain 5% to 10%) increased significantly, which means that after induction, the elastic modulus of the sodium alginate and its composite hydrogel was greatly improved, making the sodium alginate and its composite hydrogel harder, thus obtaining better mechanical strength. Figure 8 It can be clearly seen that the elastic modulus of the sodium alginate-based hydrogel samples prepared in this application is much higher than that of sodium alginate-based hydrogel samples from other sources. Specifically, the elastic modulus of the sodium alginate-based hydrogel samples after induction treatment is about 35 times higher than that before induction. This shows that the method of the present application not only improves the mechanical strength of the material itself, but also has obvious performance advantages over similar materials in the prior art. This enhanced mechanical property is very important for practical applications. For example, in the field of food packaging, it is necessary to ensure that the label can withstand certain physical stresses without being damaged.
[0049] This application also tests the colorimetric response and sensitivity of sodium alginate-based hydrogel to ammonia. The sample was placed in a glass culture dish and a 1.4% ammonia solution (800mM) was added. The color change of the sample was recorded, and AdobePhotoshop CC 2019 was used to obtain the color parameters (L*, a*, b*) and (R, G, B) of the label color. Among them, Fig. 9 This is the colorimetric response result of sodium alginate and its composite hydrogel to ammonia before induction; Fig.10 This is a colorimetric response result diagram of induced sodium alginate and its composite hydrogel to ammonia. After comparison, it was found that through this method, the color development effect of the sodium alginate-based composite hydrogel colorimetric label is more uniform.
[0050] Fig.11 This is the sensitivity result diagram of sodium alginate and its composite hydrogel before induction; Fig.12 This is a graph showing the sensitivity results of sodium alginate and its composite hydrogel after induction. Fig.12 In the experiment, the sensitivity of the induced sodium alginate and its composite hydrogel was significantly improved. After comparison, it was found that the sensitivity of the induced sodium alginate composite hydrogel was increased by about 16% at most compared with the sodium alginate hydrogel.
[0051] In order to further quantify the resolution of the colorimetric label, the colors in the distribution matrix of the color development area are calculated by taking points to obtain an RGB three-coordinate scatter plot. The aggregation trend of the points in the scatter plot can quantitatively reflect the color development uniformity of the colorimetric label, that is, the colorimetric resolution. Fig.13 The quantitative comparison results of the color uniformity of sodium alginate and its composite hydrogel before and after the induction process are shown. The figure quantifies the color resolution of the reaction colorimetric label in the form of an RGB three-coordinate scatter plot. Fig.13 As shown, the points in the scatter plot of the colorimetric response results of the samples that have not been treated by the induction process are in a state of large dispersion, that is, the distance between the points is large, and the aggregation trend is not obvious. Due to the wide distribution of the points, this indicates that the color parameters (such as RGB values) in different regions are quite different, which means that the distribution of the color developer in the entire hydrogel is not uniform, resulting in obvious regional differences in color response. In the samples treated by the induction process, the points in the scatter plot are more closely clustered together, forming clearer clusters, showing a smaller degree of discreteness. The tightly clustered points indicate that the differences in color parameters between different regions are reduced, which also proves that the distribution of the color developer in the hydrogel is more uniform, making the response of the entire label to environmental changes more consistent. In addition, as the color uniformity increases, the sensitivity of the sample to environmental changes also increases, and it can more accurately reflect small environmental changes. Higher resolution means that even at low concentrations, fast and accurate color changes can be achieved.
[0052] In summary, this method greatly improves the colorimetric response sensitivity and uniformity of color change of sodium alginate composite hydrogel, that is, the resolution of colorimetric change is higher, revealing the importance of induction process for improving label sensitivity and resolution.
[0053] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing an alginate-based hydrogel colorimetric label, characterized in that: The preparation method comprises: adding alginate and a regulating material in a set ratio into an aqueous solution containing an indicator solution and glycerol, stirring and heating the solution to obtain a mixed solution; The mixed solution is prepared into an alginate hydrogel film based on a film casting method or a tape casting method; Uniformly spraying or coating the metal ion crosslinking agent on the surface of the alginate hydrogel film to perform a crosslinking treatment, and after standing, obtaining a crosslinked alginate hydrogel film; The alginate hydrogel film after cross-linking treatment is immersed in an ethanol solution, and an alginate-based hydrogel colorimetric label is obtained after solvent exchange induction with the assistance of ultrasound.
2. The preparation method according to claim 1, characterized in that: Preferably, the alginate comprises sodium alginate or oxidized sodium alginate.
3. The preparation method according to claim 1, characterized in that: The regulating material includes gelatin or agar.
4. The preparation method according to claim 1, characterized in that: The indicator solution is prepared by dissolving the indicator in anhydrous ethanol or an aqueous solution.
5. The preparation method according to claim 4, characterized in that: The indicator comprises any one or two of the following: methyl red, bromothymol blue, methylene blue, bromocresol purple and anthocyanin.
6. The preparation method according to claim 1, characterized in that: The metal ion cross-linking agent includes any one of the following: a calcium ion solution, an aluminum ion solution, and a zinc ion solution.
7. The preparation method according to claim 6, characterized in that: The concentration of the metal ion cross-linking agent is 0.25 mol / L to 0.5 mol / L.
8. The preparation method according to claim 1, characterized in that: The metal ion cross-linking agent is sprayed or coated on the surface of the sodium alginate hydrogel film for cross-linking treatment and then left to stand for 10 min to 60 min.
9. The preparation method according to claim 1, characterized in that: The concentration of the ethanol solution is 10% v / v to 30% v / v.
10. The preparation method according to claim 1, characterized in that: The assisted ultrasound time is 0.5 h to 3 h.
Citation Information
Patent Citations
Preparation method and application of hydrogel for indicating freshness of chilled meat
CN113402734A
Anti-migration hydrogel-based freshness colorimetric indication label and preparation method thereof
CN113843937A
Solvent exchange driven polyacrylamide / polysaccharide hydrogel membrane and preparation method thereof
CN116355247A
Alginate hydrogel and manufacturing method thereof
KR1020160038120A